Field trials of a food-based vaccine to protect village chickens against Newcastle disease - Aini, I.; Ibrahim, A.L.; Spradbrow, P.B. (Elsevier, 1990)
The food pellet vaccine has been shown to be effective in trials conducted under laboratory and simulated field conditions. The village chickens vaccinated with the food pellet vaccine during the field trial were protected against virulent Newcastle disease virus. The efficacy of the food pellet vaccine in the field was evaluated by challenge trial in which 60 per cent protection was obtained, or by monitoring the incidence of Newcastle disease in vaccinated and unvaccinated birds. There was no report of Newcastle disease outbreaks in the vaccinated birds during the two-year period of the field trial. The ease in administering the food pellet vaccine makes it readily accepted by the farmers.